Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.17261/pressacademia.2017.646
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents of organizational agility: organizational structure, dynamic capabilities and customer orientation

Abstract: This study aims to investigate some antecedents of organizational agility. In the literature, it is seen that studies suggest that some organizational factors provide to maintain organizational agility. Therefore, organizational structure, dynamic capabilities and customer orientation are considered as predictors of organizational agility within the scope of the study. For this purpose, the data which were collected from 176 employees in the retailing industry by the survey method were analyzed using the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Correspondingly, Kanten et al (2017) examined the effect of dynamic capability on organizational agility in the Turkish retailing industry, having collected data from 176 employees through survey method and analysed through structural equation model. The outcome of the analysis revealed that the dynamic capability dimensions positively and significantly influence the retailers' agility.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, Kanten et al (2017) examined the effect of dynamic capability on organizational agility in the Turkish retailing industry, having collected data from 176 employees through survey method and analysed through structural equation model. The outcome of the analysis revealed that the dynamic capability dimensions positively and significantly influence the retailers' agility.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Studies have shown a positive relationship between dynamic capabilities and agility (Kanten et al, 2017; Teece, 2016). Kanten et al (2017) investigated the effect of dynamic capability on organizational agility in the Turkish retailing industry. Data was collected from 176 employees through survey method and analysed through structural equation model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other researchers have advocated the relationship between organizational agility and organizational learning strategy (e.g., Saha, et al, 2017 ). Similarly, Kanten et al ( 2017 ) found learning capability to be the most important block of an organization’s human resource capabilities.…”
Section: Discussionmentioning
confidence: 94%
“…The author identifies flexibility as one of the critical capabilities for agile organizations, expanding the term to product volume flexibility, people flexibility, and organizational flexibility. Researchers generalize the most important blocks of an organization’s human resource capabilities, such as learning capability, knowledge management, efficient decision-making, and quick solution generation, as a response to changing conditions (Kanten et al, 2017 ).…”
Section: Theoretical Foundation and Hypothesesmentioning
confidence: 99%
“…The positive impact of market orientation (MO) on related agility (e.g., organizational agility, supply chain agility, business process agility, strategic agility) has been confirmed by several investigations (e.g., Kanten et al, 2017;Kurniawan et al, 2020a;Alobaidi, 2021;Suprapti and Suparmi, 2022). However, the driving role of market orientation on CA has not been specifically presented.…”
Section: Introductionmentioning
confidence: 88%